2014
DOI: 10.3390/en7095701
|View full text |Cite
|
Sign up to set email alerts
|

Performance of a Small-Scale, Variable Temperature Fixed Dome Digester in a Temperate Climate

Abstract: Small-scale digesters, similar to popular Chinese designs, have the potential to address the energy needs of smaller dairy farmers in temperate U.S. climates. To assess this potential, a 1.14 m 3 (300 gallon) modified fixed-dome digester was installed and operated, at variable temperatures (5.3 to 27.9 °C) typical of the Midwestern United States, from March 2010 to March 2011 (363 days). Temperature, gas production, and other variables were recorded. The system was fed with dilute dairy manure with 6% volatile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…In addition, little information is available on how changes in ambient temperature affect the temperature of the full-scale anaerobic digestion process. Castano et al [30] and Ihara et al [31] found an improvement in biogas production through an increase in ambient temperature in the field-scale digester. Kalia et al [32] examined the performance of the dome biogas plant under seasonal temperature fluctuations and found that declining temperatures from summer to winter results in lowering digester temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, little information is available on how changes in ambient temperature affect the temperature of the full-scale anaerobic digestion process. Castano et al [30] and Ihara et al [31] found an improvement in biogas production through an increase in ambient temperature in the field-scale digester. Kalia et al [32] examined the performance of the dome biogas plant under seasonal temperature fluctuations and found that declining temperatures from summer to winter results in lowering digester temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Micro-scale AD development and study started during the 1970s in China and India [9] where about 30 million anaerobic digesters are nowadays installed to meet basic energy needs of rural farm families [10,11]. Depending on climate conditions, geographical situation and type of waste treated, three main technologies are used: the fixed dome digester, the floating drum digester and the plug flow or tubular digester [12].…”
Section: Introductionmentioning
confidence: 99%
“…However, after improving the above listed technical and environmental weaknesses, the development of simple and affordable micro-scale AD processes may have potential to contribute meeting the energy needs of urban areas in temperate countries. A first example was performed in Midwestern United States, where a modified and completely buried fixed-dome digester was installed inside a greenhouse [10]. Results showed that the ambient and digester temperatures ranged between − 13.5 to 35 °C and 5.3 to 27.9 °C respectively along a year, which highlights the positive effect of burying the digester to limit temperature variations of the process.…”
Section: Introductionmentioning
confidence: 99%
“…22 to 13 • C. Ihara et al [23] observed improvement in biogas production with an increase in ambient temperature in a field-scale digester in Japan. Castano et al [24] evaluated the performance of a small-scale fixed-dome digester in a temperate U.S. climate for 363 days. They observed that the digester temperature below 20 • C produced less biogas than expected.…”
Section: Introductionmentioning
confidence: 99%
“…Besides these studies, the knowledge of seasonal temperature effect on commercial-scale digesters in Bangladesh context to date is insufficient. Moreover, studies devoted to poultry manure as a feedstock are even scarcer, with very few previous studies [22,24] reporting the performance of digesters treating cattle manure only. To address this research gap, the aim of the current work was to investigate the effect of seasonal temperature variations on the digester temperature and biogas quality by using a fixed-dome biogas digester treating local poultry litter in Bangladesh conditions.…”
Section: Introductionmentioning
confidence: 99%